2021
DOI: 10.3389/fimmu.2021.711621
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ADAM17 by IL-15 Limits Human NK Cell Proliferation

Abstract: Natural killer (NK) cells are innate cytotoxic lymphocytes that can recognize assorted determinants on tumor cells and rapidly kill these cells. Due to their anti-tumor effector functions and potential for allogeneic use, various NK cell platforms are being examined for adoptive cell therapies. However, their limited in vivo persistence is a current challenge. Cytokine-mediated activation of these cells is under extensive investigation and interleukin-15 (IL-15) is a particular focus since it drives their acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…On the other hand, Pham et al showed that the treatment of NK cells with the ADAM17 inhibitor (TAPI-1) increases the purity of NK cells expanded ex vivo, the expression of CD16 (FcγRIII), IFN-γ production and improves antibody-dependent cytotoxicity activity against breast cancer cells. These data do not indicate that blocking ADAMs proteases may have a dual role and provide a new approach enhancing the persistence and function of NK cells in cancer patients [82][83][84][85][86][87][88][89][90].…”
Section: Treatments That Enhance Nk Cell Activitymentioning
confidence: 81%
“…On the other hand, Pham et al showed that the treatment of NK cells with the ADAM17 inhibitor (TAPI-1) increases the purity of NK cells expanded ex vivo, the expression of CD16 (FcγRIII), IFN-γ production and improves antibody-dependent cytotoxicity activity against breast cancer cells. These data do not indicate that blocking ADAMs proteases may have a dual role and provide a new approach enhancing the persistence and function of NK cells in cancer patients [82][83][84][85][86][87][88][89][90].…”
Section: Treatments That Enhance Nk Cell Activitymentioning
confidence: 81%
“…Interestingly, whilst IL-15 significantly increased the frequencies of cells expressing L-selectin and α4β7, simultaneous exposure to fractalkine undermines these effects, suggesting that fractalkine antagonises the stimulatory effects of IL-15 in relation to enhanced adhesion molecule expression. Previous work has shown short term stimulation with IL-15 increases L-selectin expression on NK cells, while a recent report has shown longer term stimulation can decrease L-selectin expression which can stifle NK cell expansion [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another candidate is ADAM17, which is activated through the IL-15 axis and reduces NK cell proliferation. Blockade of this metalloproteinase results in increased levels of L-selectin (CD62L) on NK cells, thus supporting the homing of these cells (176). However, not only downregulation of the IL-15R function, but also chronic exposure to IL-15 leads to the NK cell exhaustion (177).…”
Section: Impairment Of Nk Cell Developmentmentioning
confidence: 99%